Bullous pemphigoid associated with dipeptidyl peptidase‐4 inhibitor showing unfavorable outcomes despite immediate discontinuation of medication. Issue 10 (30th August 2020) - Shinohara, Yasutake; Iijima, Toshie; Sakurai, Shintaro; Jojima, Teruo; Ohira, Eriko; Hayashi, Shujiro; Usui, Isao; Igawa, Ken; Aso, Yoshimasa
Abstract: We experienced two cases of dipeptidyl peptidase‐4 (DPP‐4) inhibitor‐associated bullous pemphigoid (BP) showing an unfavorable course despite its discontinuation. Clinicians should carefully monitor the course of DPP‐4 inhibitor‐associated BP even after withdrawal of DPP‐4 inhibitor therapy, especially in very elderly patients. Abstract : We experienced two cases of dipeptidyl peptidase‐4 (DPP‐4) inhibitor‐associated bullous pemphigoid (BP) showing an unfavorable course despite its discontinuation. Clinicians should carefully monitor the course of DPP‐4 inhibitor‐associated BP even after withdrawal of DPP‐4 inhibitor therapy, especially in very elderly patients.